The Effect of Work Stress and Emotional Intelligence on Self-leadership among Nurses in Leadership Positions in the Lesotho Ministry of Health and Social Welfare - van Zyl, Ebben Stegmann; Mokuoane, M; Nel, Petrus (Africa Journal of Nursing and Midwifery, 2017)
The current work environment increasingly requires independent individuals who are able to take the initiative and make responsible decisions in settings where they are not always supported by hierarchical superiors. In this context, the concept of self-leadership has been linked to professional and personal effectiveness. This study investigated the theory of self-leadership and factors that have an impact on the quality and use of the individual’s self-leadership, namely work stress and emotional intelligence. For this purpose, a sample of 159 nursing leaders working at the Lesotho Ministry of Health and Social Welfare was selected. Self-leadership, work stress and emotional intelligence were measured using the Revised Self-leadership Questionnaire, the Experience of Work and Life Circumstances Questionnaire, and the Emotional Intelligence Index, respectively. Statistical analyses such as stepwise multiple regression analysis, correlations and a t-test were applied to determine the effect of work stress and emotional intelligence on self-leadership. Results indicate that the variance in self-leadership (total) scores can be attributed to EQI (self-regulation) and causes of work stress (physical working conditions). The independent t-test results also indicate no statistically significant differences in self-leadership between the different age groups in the sample. In the light of these findings, a few recommendations are made.